Balanced Scorecard Analysis as An Alternative Management Performance Measuring Tool: Case Study - Heru Ariwibowo (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2023)
The aim of this research is to analyze the performance of the Vocational Education Quality Assurance Development Center in the field of Marine, Fishery, Information and Communication Technology using the Balance Scorecard Perspective approach which analyzes four perspectives; financial, customer (in this case educators and education staff), internal business processes, and learning and growth. The research method was carried out qualitatively. The sample in this research is the financial report of the Center for Vocational Education Quality Assurance Development in the Maritime, Fishery, Information and Communication Technology sector (BPPMPV KPTK).